Effectiveness of lifestyle interventions in preventing progression from prediabetes to diabetes - Yaqoub, Marwah; Aljazeeri, Ali; Alqahtani, Khalid; Alsalmi, Gharam; Badoghaish, Samah; Arishi, Rayed; Alluhaybi, Ahmed; Alwalan, Ali; Ismail, Ranya; Aldalwi, Muntathir (International Journal Of Community Medicine And Public Health, 2026)
Prediabetes, a state of intermediate hyperglycemia, significantly increases the risk of developing type 2 diabetes mellitus and associated complications. With global prevalence on the rise, early intervention is critical to reduce the long-term health and economic burden of diabetes. Lifestyle modification remains the most effective non-pharmacological approach for preventing the progression from prediabetes to diabetes. Interventions focusing on dietary changes, increased physical activity, and weight reduction have demonstrated substantial improvements in glycemic control, particularly in structured and intensive programs. Clinical trials such as the Diabetes Prevention Program and the Finnish Diabetes Prevention Study have shown that lifestyle interventions can reduce diabetes incidence by more than 50 percent among high-risk individuals. Despite strong evidence, real-world implementation reveals challenges in long-term adherence and program scalability. Multiple factors influence outcomes, including individual motivation, cultural relevance, socioeconomic constraints, and healthcare access. Programs tailored to the needs and preferences of specific populations show better retention and engagement. Digital tools and community-based approaches have expanded accessibility, although technological barriers and variability in engagement persist. Sustained impact often relies on ongoing support and integration with primary care and public health systems. From a public health perspective, creating environments that support healthy behaviors is essential for sustaining lifestyle changes. Policy measures that improve food access, promote physical activity, and encourage preventive care can reinforce individual-level efforts. Cost-effectiveness analyses support investment in lifestyle programs, particularly when targeted at high-risk groups. Long-term sustainability depends on aligning intervention design with both personal and structural determinants of health. While lifestyle change is often viewed as an individual responsibility, its success is shaped by systems and environments that either support or hinder behavior over time. Addressing these broader influences remains key to reducing the global burden of diabetes through prevention.